Beta and Sigma Convergence Analysis of Inclusive Economic Growth on National and Regional Economic Growth in Indonesia - Anjani, Ika Resti; Prasetyo, P Eko (Future Science / FSH-PH Publications, 2024)
This study aims to determine the occurrence of convergence in inclusive economic growth at both the national and regional levels, as well as the factors that drive the increase in inclusive economic growth to reduce regional disparities. The analysis used is sigma convergence, absolute beta convergence, and conditional beta convergence. The data used is a panel consisting of 21 provinces in the Western Region of Indonesia (KBI), including Sumatra, Java and Kalimantan, 13 provinces in the Eastern Region of Indonesia (KTI), namely Sulawesi, Nusa Tenggara and Bali, Maluku and Papua, as well as national level consisting of 34 provinces in Indonesia from 2017 to 2021. This study shows that at the national level, KBI and KTI, there has been both sigma convergence and absolute beta convergence. Conditional beta convergence only occurs at the national level and KBI. Meanwhile, in KTI, there is no process of conditional beta convergence or what can be called divergence occurring. Variables that significantly affect the convergence process at the national level include government expenditure in the economic, health, and social protection sectors, domestic investment, and the open unemployment rate. At the KBI, significant factors include government expenditure in social protection sectors domestic investment and the unemployment rate. At the KTI, significant factors include government expenditures on the economic, health, and social protection sectors, foreign investment, and the unemployment rate.